2016
DOI: 10.1002/pon.4194
|View full text |Cite
|
Sign up to set email alerts
|

Links between personality, time perspective, and intention to practice physical activity during cancer treatment: an exploratory study

Abstract: The present exploratory study with patients suffering from cancer underlined the importance of considering jointly time perspective dimensions and personality factors for health behavior recommendations. Based on our results, we propose some reflections on practice to help nurses and physicians increase patient's motivation to be physically active. Taking into account patients' personality and time perspective, we would be able to propose specific awareness messages and offer short interventions to have an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Our study was focused on examining self-care behaviors rooted in the daily lives of patients with gastrointestinal cancer and showed that openness was signi cantly associated with the implementation of activity adjustment and ingenuity towards changes in appearance. Previous studies have shown that the intent of exercise is associated with a high degree of openness in patients undergoing chemotherapy [23]; this nding is in agreement with our results that suggest a moderately signi cant positive correlation of openness with adjustment of exercise. Those with a high degree of openness are not bound by existing values and are characterized by actively working on new situations [21][22][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…Our study was focused on examining self-care behaviors rooted in the daily lives of patients with gastrointestinal cancer and showed that openness was signi cantly associated with the implementation of activity adjustment and ingenuity towards changes in appearance. Previous studies have shown that the intent of exercise is associated with a high degree of openness in patients undergoing chemotherapy [23]; this nding is in agreement with our results that suggest a moderately signi cant positive correlation of openness with adjustment of exercise. Those with a high degree of openness are not bound by existing values and are characterized by actively working on new situations [21][22][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…Second, findings disclosed that rehabilitants high in Conscientiousness are more effective in translating their plans into physical activity than rehabilitants with low or moderate levels of Conscientiousness. Prior studies already revealed that Conscientiousness increases the likelihood for rehabilitants to act in line with their intentions (Rhodes & Dickau, 2013; Villaron et al, 2017). Our results add further evidence to these findings by showing that a strong intention-behavior relationship in rehabilitants high in Conscientiousness might be a result of their planning strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous studies, we examined the association of Conscientiousness and planning in a longitudinal observational study. Conscientious rehabilitants are purposeful and thorough (e.g., Villaron et al, 2017) and are good at translating their intentions into behavior (e.g., Rhodes & Dickau, 2013). Planning, in turn, is a strong determinant for the adoption and maintenance of physical activity after rehabilitation.…”
Section: Conscientiousness and The Intention-planning-behavior Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…As Simons and colleagues note, “deep future time perspective and increasing the instrumentality of one’s present behavior are associated with enhanced motivation, (...), better performance, and more intensive persistence” (Simons et al, 2004, p. 121). Although empirically confirmed mainly within the educational context, this statement appears to be universal, and motivational consequences of future focus should be analogical within the domain of sport activity, especially taking into account that Future-oriented individuals exhibit particularly high intention–behavior consistency (Van Ittersum, 2012; Villaron et al, 2017). The latter effect was demonstrated in multiple life areas, including quitting smoking (Kovač and Rise, 2007), weight control (Vinkers et al, 2013), or even participation in longitudinal research (Harber et al, 2003), and given that in sport such consistency is of particular importance (Theodorakis, 1994), analogical effects in this domain may be even more pronounced.…”
Section: The Present Conceptual Modelmentioning
confidence: 89%